1994
DOI: 10.1007/bf02355669
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with homework assignments in cognitive-behavioral psychotherapy for depression: Relation to outcome and methods of enhancement

Abstract: Despite the importance attached to homework in cognitive-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 22 publications
0
55
1
1
Order By: Relevance
“…However, Startup and Edmonds (1994) found no significant relationship between these variables and compliance and suggested that their negative findings reflected variation in patient requirements for particular therapist behaviours. For example, hopeless clients may respond adversely to attempts to involve them in identifying homework tasks but respond more positively to therapist-allocated tasks, whereas more resourceful clients may have exactly opposite reactions, welcoming choice and resisting allocated assignments.…”
Section: Introductionmentioning
confidence: 74%
“…However, Startup and Edmonds (1994) found no significant relationship between these variables and compliance and suggested that their negative findings reflected variation in patient requirements for particular therapist behaviours. For example, hopeless clients may respond adversely to attempts to involve them in identifying homework tasks but respond more positively to therapist-allocated tasks, whereas more resourceful clients may have exactly opposite reactions, welcoming choice and resisting allocated assignments.…”
Section: Introductionmentioning
confidence: 74%
“…In two studies of therapist competency in delivering cognitive-behavior therapy for depression, therapists' competency in the review of homework assignments was correlated with homework compliance (e.g., Bryant et al, 1999;Shaw et al, 1999; also see Worthington, 1986). However, a study by Startup and Edmonds (1994) did not find any evidence to suggest that therapist adherence to the homework administration procedures was associated with compliance. Similarly, a study by Burns and Nolen-Hoeksema (1992) did not produce a significant relationship between therapist empathy and compliance.…”
Section: Therapist Factorsmentioning
confidence: 88%
“…The meta-analytic evidence of a homework-outcome relation was based on a combination of studies examining different patient populations and treatments under investigation, with these treatments differing markedly in the homework utilized. In our search for studies of homework in individual CT for depression, we identified a relatively small group of seven studies (Bryant, Simons, & Thase, 1999; Burns & Spangler, 2000; Coon & Thompson, 2003; Cowan et al, 2008; Detweiler-Bedell & Whisman, 2005; Persons et al, 1988; Startup & Edmonds, 1994). A review of these studies suggests that all but one (i.e., Detweiler-Bedell & Whisman, 2005) reported evidence of homework compliance in CT for depression being associated with positive outcomes at the end of treatment.…”
mentioning
confidence: 99%